2021
DOI: 10.7150/ijms.61697
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Perioperative Massive Transfusion on Long Term Outcomes of Liver Transplantation: a Retrospective Cohort Study

Abstract: Background: Liver transplantation (LT) is associated with a significant risk of intraoperative hemorrhage and massive blood transfusion. However, there are few relevant reports addressing the long-term impacts of massive transfusion (MT) on liver transplantation recipients. Aim: To assess the effects of MT on the short and long-term outcomes of adult liver transplantation recipients. Methods: We included adult patients who underwent liver transplantation at West China Hospital from January 2011 to February 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…However, the deleterious association of the transfusion starts with the first transfusion episode (1 or 2 RBC units). In previous studies, this association only appeared after the third RBC unit . The difference may either be related to a smaller number of patients or different transfusion practices in these studies.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…However, the deleterious association of the transfusion starts with the first transfusion episode (1 or 2 RBC units). In previous studies, this association only appeared after the third RBC unit . The difference may either be related to a smaller number of patients or different transfusion practices in these studies.…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, the same association of storage duration was observed in patients who had a single episode of RBCT. Although most transfusions (72%) concerned 1 or 2 RBC units, we and others reported that the harmful association of the transfusion was proportional to the number RBC unit transfused . The association between the need for a massive transfusion and severe posttransplant complications is obvious.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Studies have shown that the need for intraoperative blood transfusion is associated with an increased risk of death after liver transplantation and it is identified as the most important predictor of patient survival (Rana et al, 2013;Cleland et al, 2016;Viguera et al, 2021). A cohort study found that patients who received MT during the perioperative period of liver transplantation had a worse long-term prognosis than non-MT patients, with higher 30-day mortality and complication rates (Tan et al, 2021). Besides, the economic pressure and disease transmission risk brought by MT will further increase.…”
Section: Introductionmentioning
confidence: 99%